2019
DOI: 10.12973/ijem.5.1.59
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Homophobia and Unconditional Self-Acceptance on Respect of Differences in Psychological Counselor Candidates

Abstract: This research was conducted to investigate the predictive role of homophobia and unconditional self-acceptance on respect of differences in psychological counselor candidates. Participants were 239 psychological counselor candidates. The Respect of Differences Scale, the Homophobia Scale, and the Unconditional Self-Acceptance Scale were used to collect the data. Path analysis was used to determine the influences of variables on respect of differences. The independent sample t-test and one-way ANOVA were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Research on unconditional self-acceptance found that a low level of unconditional self-acceptance correlates with depression, anxiety, anger, and neuroticism (Popov, 2019;Prihadi et al, 2019;Andronikos, 2021). High levels of unconditional self-acceptance were in general strongly related to mental health, happiness, self-esteem, life satisfaction, well-being, respect for the differences between individuals, and low levels of anxiety and depression (Vural-Batik, 2019;Bernard M. E., 2020). Unconditional self-acceptance also correlates positively with dispositional forgiveness (Porada et al, 2018), self-compassion and flourishing (Venet, 2019;Andronikos, 2021).…”
Section: Teachers' Unconditional Self-acceptancementioning
confidence: 99%
“…Research on unconditional self-acceptance found that a low level of unconditional self-acceptance correlates with depression, anxiety, anger, and neuroticism (Popov, 2019;Prihadi et al, 2019;Andronikos, 2021). High levels of unconditional self-acceptance were in general strongly related to mental health, happiness, self-esteem, life satisfaction, well-being, respect for the differences between individuals, and low levels of anxiety and depression (Vural-Batik, 2019;Bernard M. E., 2020). Unconditional self-acceptance also correlates positively with dispositional forgiveness (Porada et al, 2018), self-compassion and flourishing (Venet, 2019;Andronikos, 2021).…”
Section: Teachers' Unconditional Self-acceptancementioning
confidence: 99%